Simultaneous quantification of acylated and desacylated ghrelin in biological fluids - Aydin, Suleyman; Karatas, Fikret; Geckil, Hikmet (Wiley, 2008)
This study reports simultaneous quantification of both acylated and desacylated forms of ghrelin in biological samples, utilizing a reverse-phase high-performance liquid chromatography (HPLC) system. The HPLC assay was also compared with RIA assays in use. Biological samples (serum, saliva, urine, milk) known for the presence of ghrelin were collected from a total of eight post-partum women and eight male volunteers. Analysis of ghrelin with HPLC was also validated for linearity, precision, detection limit and accuracy. An elution time of 6 min was observed for pure (commercial) desacylated human ghrelin and for the same form of the hormone from all body fluids studied. The elution time for acylated pure human ghrelin and that in body fluids, however, was around 16 min. The mean recovery rate was over 90% for both forms with no significant interference. The lowest detectable levels for acylated and desacylated ghrelin with the method used here were 11 (+/- 2) and 14 (+/- 3) pg mL(-1), respectively. Given its simplicity, accuracy, time and cost-effectiveness, the HPLC method described here for determination of two forms of ghrelin (active and inactive) might prove useful for certain diagnostic purposes. Copyright (C) 2008 John Wiley & Sons, Ltd.
Keywords: lipopeptides; ghrelin; desacylated ghrelin; acylated ghrelin; n-octanoylation